The Use of administrative record linkage to examine patterns of universal early childhood health and education service use from birth to Kindergarten (age 4 years) and developmental vulnerability in the Preparatory Year (age 5 years) in Tasmania, Australia. - Taylor, Catherine Louise; Christensen, Daniel; Venn, Alison; Preen, David; Stafford, Joel; Hansen, Emily; Jose, Kim; Zubrick, Stephen (International Journal of Population Data Science, 2022)
Background In Australia, the health and education sectors provide universal early childhood services for the same population of children. Therefore, there is a strong imperative to view service use and outcomes through a cross-sectoral lens to better understand and address the service needs of young children and their families. Objectives To investigate patterns of health and education service use from birth through Kindergarten (age four years), the associations with cumulative risks, and developmental vulnerability in the first year of full-time school (age five years). Methods A retrospective cohort study that used population-wide linkage of health and education administrative data records for 5,440 children with a Tasmanian 2015 Australian Early Development Census (AEDC) record who were born in Tasmania (2008-2010). Results Four service use patterns were identified: Regular (46% of children), Declining (24%); Low (18%); and Selective service use (12%). Regular service use (aOR 0.8, 95% CI 0.7 to 0.9), adjusted for cumulative risks, was associated with decreased odds of developmental vulnerability, compared to the other service use groups. Low (OR 6.1, 95% CI 4.5 to 8.2) and Declining service use (OR 2.5 95% CI 1.9 to 3.4) were more likely for children with the highest levels of cumulative risks. Low and Declining service use, adjusted for cumulative risks were associated with increased odds of developmental vulnerability, compared to the Regular service use group. Conclusion This study provides a whole population view of the differential use of universal services and the complex risk circumstances that influence service use. The association between patterns of multiple risk and service use points to barriers to service use, and the varying level of developmental vulnerability within each service use group draws attention to children who may benefit from higher sustained participation in core health and education services across the whole of early childhood.